Numerical Solution of a Class of Time-Fractional Order Diffusion Equations in a New Reproducing Kernel Space - Xiaoli Zhang; Haolu Zhang; Lina Jia; Yulan Wang; Wei Zhang (Journal of Function Spaces)
In this paper, we structure some new reproducing kernel spaces based on Jacobi polynomial and give a numerical solution of a class of time fractional order diffusion equations using piecewise reproducing kernel method (RKM). Compared with other methods, numerical results show the reliability of the present method.